American jihadi terrorism: A comparison of homicides and unsuccessful plots. Issue 3 (4th May 2019) - Gruenewald, Jeff; Klein, Brent R.; Freilich, Joshua D.; Chermak, Steven
ABSTRACT: While the number of American jihadi terrorist attacks remains relatively rare, terrorist plots thwarted by law enforcement have increased since September 11, 2001. Although these law enforcement blocks of would-be terrorists are considered counterterrorism triumphs by the FBI, human rights and civil liberty watch groups have conversely suggested that those who plan for attacks alongside government informants and undercover agents may be unique and essentially dissimilar from terrorists. Underlying this debate is the empirical question of how planned yet unsuccessful attacks and their plotters compare to successful terrorist homicides and their perpetrators. The current study addresses this question by comparatively examining jihadi terrorist homicides and unsuccessful plots occurring in part or wholly on U.S. soil between 1990 and 2014. Data for this study come from the U.S. Extremist Crime Database (ECDB), an open-source database with information on terrorism and extremist crimes. Based on these data, descriptive statistics are provided for several incident, offender, and target variables across three jihadi terrorist violence categories, including homicides, plots with specified targets, and plots with non-specific targets. We find several important differences across categories of terrorist violence, suggesting that unsuccessful plotters and their intended crimes vary from their more successful terrorist counterparts.